The Role and Principle of Muhammadiyah Ideology in the Nation and State: Historical Studies - Merlinda, Riza; Nurhakim, Moh. (HISTORIA: Jurnal Program Studi Pendidikan Sejarah, 2025)
Muhammadiyah's ideology is a movement for tajdid, or renewal, in all aspects of human life using Islamic theories and systems. This movement always has an agenda of progress (Iṣlah). Muhammadiyah's ideology is structured into thoughts or principles stated in the Muqaddimah of Muhammadiyah's Articles of Association, Muhammadiyah's personality, Muhammadiyah's Faith and Life Ideals, Muhammadiyah's Khittah and other formal thoughts. The methodology used in this research uses the library method (library research), while data collection is carried out by reviewing or exploring several journals, books and documents as well as other sources of data and information that are considered relevant to the research. The findings in this research are the Muhammadiyah ideology as the foundation and main orientation of the movement. In Muhammadiyah ideology, it can be understood as a system of understanding or belief and a theory of struggle to implement Islamic teachings in the lives of the people through socio-religious movements. The main idea or stance in question has been conceptualized in the content of Muhammadiyah's ideology in the Muqaddimah of Muhammadiyah's Articles of Association. The importance of Muhammadiyah ideology in national and state life must adhere to the Islamic Life Guidelines for Muhammadiyah Citizens (PHIW).